The theological programme of Mark: exegesis and function of Mark 1:1,2-15 - Filannino, Francesco (Wissenschaftliche Untersuchungen zum Neuen Testament / 2, 2021)
"The first chapters of literary works are indispensable to understanding them. This is also true of the Gospels. Francesco Filannino shows that the introductory section of Mark's Gospel (Mark 1:1-15) is an important key to accessing the whole narrative, because it anticipates the main contents of the evangelist's theology."